2009
DOI: 10.1210/jc.2008-2665
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Metabolic Syndrome in Children and Adolescents

Abstract: Cutoff-point-based definitions for pediatric metabolic syndrome have substantial instability in the short and long term. The value of making a cutoff-point-based diagnosis of metabolic syndrome during childhood or adolescence remains in question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 40 publications
3
56
4
1
Order By: Relevance
“…These data are consistent with findings from other studies that demonstrate the relative short-and longer-term instability in the diagnosis of youth MetS (3,6,7). Several factors might contribute to this.…”
Section: Figure 1 Meta-analysis Forest Plots For High Carotid Intima-supporting
confidence: 92%
See 1 more Smart Citation
“…These data are consistent with findings from other studies that demonstrate the relative short-and longer-term instability in the diagnosis of youth MetS (3,6,7). Several factors might contribute to this.…”
Section: Figure 1 Meta-analysis Forest Plots For High Carotid Intima-supporting
confidence: 92%
“…A recent consensus statement (2) has called for more research, particularly in longitudinal studies from youth to adulthood, on a number of areas relating to pediatric MetS before a definition for the clinical diagnosis of MetS among youth is considered. Some of the unwillingness to issue a definite definition is due to concerns over the demonstrated short-term instability of a categorical diagnosis of MetS in the pediatric setting (6,7). Further to this, however, is that-irrespective of instability-the ability to predict future disease status is critically important.…”
mentioning
confidence: 99%
“…A consensus definition and criteria for the diagnosis of the metabolic syndrome in adults has been established; (41) the diagnosis of the metabolic syndrome in adolescents, with a significant number of adolescents failing to meet diagnostic criteria upon long-term follow-up. (44,45) Long-term follow-up of a cohort of children ages 6 to 19 years of age from the Cincinnati clinic of the National Heart, Lung, and Blood Institute LRC Prevalence Study demonstrated an association between a diagnosis of the metabolic syndrome during childhood, as defined by a BMI ≥ the age-specific 90 th percentile and the following criteria:…”
Section: Inflammation and Obesitymentioning
confidence: 99%
“…Porém, é importante reconhecer que um enfoque na síndrome metabólica, em vez de nos fatores de risco individuais, pode destoar da abordagem mais eficaz de cuidados preventivos ou tratamento. Primeiro, a síndro-me metabólica não se mantém ao longo da infância 6,7 , da infância para o início da vida adulta 8 e particularmente em crianças nas categorias de risco maior 9 . Por consequência, importantes órgãos consultivos levantaram dúvidas sobre sua utilidade em crianças 10 .…”
Section: Metabolic Syndrome In Childrenunclassified